2004
DOI: 10.1038/oby.2004.43
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Body Weight and Plasma Ghrelin Levels after Gastric Banding and Gastric Bypass

Abstract: STOECKLI, ROLF, ROBIN CHANDA, IGOR LANGER, AND ULRICH KELLER. Changes of body weight and plasma ghrelin levels after gastric banding and gastric bypass. Obes Res. 2004;12:346 -350. Objective: Ghrelin is an enteric peptide with strong orexigenic and adipogenic effects. Plasma ghrelin levels are decreased in obese subjects but increase after weight loss; this increase is not observed after Roux-en-Y gastric bypass (RYGB). Prospective and comparative data after adjustable silicone gastric banding (ASGB) have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 25 publications
8
127
0
3
Order By: Relevance
“…Fasting ghrelin levels have been found to increase 2 years after vertical banded gastroplasty [38] and in patients who attained 20% body mass index (BMI) loss [39]. Likewise, in obese patients 6 months [9,16,18,19,40,41], 12 months [17,19,40], and 24 months [38,40] after being submitted to adjustable gastric banding, fasting ghrelin levels have been shown to increase, similarly to diet induced weight loss, although the increase in ghrelin levels was greater after surgery than after dietinduced weight loss, and this could be explained by the higher amount of weight loss achieved with surgery. Furthermore, postoperative ghrelin levels were also reported as not being different from those of non-operated BMImatched patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Fasting ghrelin levels have been found to increase 2 years after vertical banded gastroplasty [38] and in patients who attained 20% body mass index (BMI) loss [39]. Likewise, in obese patients 6 months [9,16,18,19,40,41], 12 months [17,19,40], and 24 months [38,40] after being submitted to adjustable gastric banding, fasting ghrelin levels have been shown to increase, similarly to diet induced weight loss, although the increase in ghrelin levels was greater after surgery than after dietinduced weight loss, and this could be explained by the higher amount of weight loss achieved with surgery. Furthermore, postoperative ghrelin levels were also reported as not being different from those of non-operated BMImatched patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that the suppressed ghrelin levels contribute to the weight-reducing effect of the surgery. Leonetti et al 17 and Tritos et al 18 also reported lower ghrelin values in operated patients compared with matched controls, and in patients studied pre-and postoperatively decreased ghrelin levels 19,20 or unchanged levels 21 have been shown compared with the preoperative state. In contrast, we observed increased ghrelin levels in 40 out of 53 patients and in 60 out of 66 patients 6 and 12 months after gastric bypass surgery, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…Cummings and colleagues had hypothesized that ghrelin cells in the gastric mucosa may eventually cease to secrete ghrelin, as they are constantly stimulated by an empty stomach (override inhibition hypothesis) (Cummings et al, 2004). However, some doubt is cast on this explanation by reports of unchanged (Stoeckli et al, 2004), or even increased (Holdstock et al, 2003) ghrelin levels after RYGB, and by the observation in rats, that postprandial ghrelin suppression does not depend on nutrients in the stomach, but on nutrients in the duodenum and proximal jejunum (Williams et al, 2003a). Reflux of nutrients from the bypass limb into the proximal jejunum could thus still trigger prandial ghrelin suppression, rendering the override inhibition hypothesis doubtful.…”
Section: Vagal Mechanisms Affected By Obesity Surgeriesmentioning
confidence: 99%